IDENTIFIKASI ANATOMI DAN MORFOLOGI MANGGA (Mangifera indica L.) LOKAL DESA TOBOLI INDUK DAN DESA OLAYA KABUPATEN PARIGI MOUTONG - Rizal, Sesaiful; Maemunah, Maemunah; Adrianton, Adrianton (AGROTEKBIS, 2018)
Mango (Mangifera indica L) is a kind of anually fruit tree which come from India. The main purpose of this research is to examining and identifying a morphology and structure of local manggo at Central Toboli Village, Subdisctrict North Parigi, and Olaya Village in subdistrict Parigi The regency of Parigi Maoutong as a pioneer of a mother of the plant. This research is held at central Toboli Village and Olaya village the regency of Parigi Moutong and was continued at a Biology Laboratory of MIPA faculty Tadulako University, July untill August 2016. This research is using a survey method, the first activity is taking a decision of a location of research, the location of research is decided intentionally (purpose sampling) base on information from Agriculture Departement and the local resident and also concerning to see the influenses a manggo plant base on the result of the surveyfrom several subdistrict, that those subdistrict has many vegetations of manggo plants compared to other location. The result shows that there are many choosen access from several villages of subdistrict of Parigi and North Parigi according to characteristic of Morfology, structure, stem, and the leaves structure of Manggo plant which represented by two accesses averagely from each village. At central toboli at 0.695 achieved by two choosen accesses, they are TBI8 and TBI2. Olaya village has two accesses, they are OLY4 and OLY5 and at the combination of those two villages represented by the access of TBI8 and OLY4. Keyword: Anatomy, Mango, Morphology.